2017
DOI: 10.1536/ihj.16-332
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cilostazol on the Angiographic Outcome of Drug-Eluting Coronary Stents Angiographic Analysis of the CILON-T (Influence of CILostazol-Based Triple Antiplatelet Therapy ON Ischemi Complication after Drug-Eluting StenT Implantation) Trial

Abstract: SummaryIt is not clear if anti-restonotic effect of cilostazol is consistent for different types of drug-eluting stents (DES).The purpose of this study was to compare the anti-proliferative effect of cilostazol between DAT and TAT with consideration of confounding influences of DES type.Nine hundred and fifteen patients were randomized to either dual antiplatelet therapy (DAT; aspirin and clopidogrel) or triple antiplatelet therapy (TAT; aspirin, clopidogrel, and cilostazol) in the previous CILON-T trial. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Lesion length (≥28 mm; HR, 2.10), and platelet reactivity unit level at hospital discharge (every rise in tertile, HR, 1.61) were predictors of the primary end point; however, using cilostazol was not (HR, 0.90). In a subsequent analysis of this trial, it was reported that triple therapy significantly decreased in‐stent late loss ( P = .015) 177 . There was no interaction of stent type, lesion length, or diabetes with difference of late loss.…”
Section: Coronary Artery Diseasementioning
confidence: 80%
See 1 more Smart Citation
“…Lesion length (≥28 mm; HR, 2.10), and platelet reactivity unit level at hospital discharge (every rise in tertile, HR, 1.61) were predictors of the primary end point; however, using cilostazol was not (HR, 0.90). In a subsequent analysis of this trial, it was reported that triple therapy significantly decreased in‐stent late loss ( P = .015) 177 . There was no interaction of stent type, lesion length, or diabetes with difference of late loss.…”
Section: Coronary Artery Diseasementioning
confidence: 80%
“…In a subsequent analysis of this trial, it was reported that triple therapy significantly decreased in-stent late loss (P = .015). 177 There was no interaction of stent type, lesion length, or diabetes with difference of late loss. However, cilostazolconferred decrease of late loss did not significantly reduce the rate of revascularization (7.8% vs 6.9%; P = .69).…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 85%
“…These clinical benefits of cilostazol have been attributed to its additional platelet inhibition on top of DAPT in PCI-treated patients. However, high on-clopidogrel platelet reactivity was more convincingly associated with the risk of stent thrombosis but less with in-stent restenosis [23,33,34]. EPC as a key effector of endothelial regeneration has been significantly associated with the risks of revascularization and thrombotic events after PCI [16].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples on day 2 were obtained after 12 to 24 hours from the study drug administration, according to previous studies. [17][18][19] Aspirin (100 mg/d) was maintained irrespective of other antithrombotic medications, and the use of ticagrelor (90 mg twice a day), CLP (75 mg/d) plus rivaroxaban (2.5 mg twice a day), or CLP (75mg/d) was maintained for 1 month. Otherwise, patients were treated as per international and local guidelines for ACS management.…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic stroke was defined as a new focal neurologic deficit of vascular origin lasting at least 24 hours that was proven to be nonhemorrhagic by either computed tomography or magnetic resonance imaging scanning. 18 Safety assessments, including the occurrence of any bleeding complications, were evaluated during follow-up according to the Bleeding Academic Research Consortium criteria. 26…”
Section: Study End Points and Clinical Follow-upmentioning
confidence: 99%